THE EFFECTS OF POPULATION GROWTH ON MORPHOLOGICAL DEVELOPMENT OF BALINESE TRADITIONAL VILLAGE : Bayung Gede Village, Kintamani District, Bangli City, Bali Province - Feliksdinata Pangasih; Amos Setiadi (Tesa Arsitektur, 2017)
Bayung Gede Village is included in one of traditional villages in Bali, which until now is still preserved. The village that becomes a pioneer of traditional village development in Bangli area has population growth that continues to increase. Population growth is also affected by awig-awig or the traditional village regulations, the education and welfare level, and the community’s economy. These conditions affect the morphological and structural development of traditional village yard because the number of the need for dwellings is proportional to the number of population growth. The problem raised is how the influences of population growth on the morphological development in Bayung Gede traditional village are. The method used was descriptive analysis by collecting data method through field observation, deep interview, and literature study. This study finds a morphological development pattern of the village that currently has a concept that still firmly holds village’s awig-awig. How ever, the pattern of the settlement growth shows more flexible tolerance to the influence of new infrastructure in the surrounding areas, where the condition of the regional morphology in the traditional village yard is triggered by population growth of Bayung Gede Village.